Volcanic and structural evolution of Pico do Fogo, Cape Verde. (31st July 2015) - Carracedo, Juan‐Carlos; Perez‐Torrado, Francisco J.; Rodriguez‐Gonzalez, Alejandro; Paris, Raphaël; Troll, Valentin R.; Barker, Abigail K.
Abstract : In recent months the media have drawn attention to the Cape Verde archipelago, with particular focus on the island of Fogo, the only island presently active and with an eruption that began on 23 November 2014, finally ceasing on 7 February 2015. The Monte Amarelo conical shield forms most of the 476 km 2 almost circular island of Fogo. After attaining a critical elevation of about 3500 m, the Monte Amarelo shield volcano was decapitated by a giant landslide that formed a caldera‐like depression (Cha das Caldeiras), which was subsequently partially filled by basaltic nested volcanism. This younger eruptive activity culminated in the construction of the 2829 m‐high Pico do Fogo stratocone, apparently entirely made of layers of basaltic lapilli. Continued growth of the Pico do Fogo summit eruptions was interrupted in 1750, most likely after the stratocone reached a critical height. Since then, at least eight eruptions have taken place inside the landslide depression at the periphery of the Pico do Fogo cone, including the 2014–2015 eruptive event. Strong geological similarities with the Canary Islands, 1400 km to the north, have been frequently noted, probably as a consequence of a common process of origin and evolution associated with a mantle hot‐spot. These similarities are particularly evident when comparing Fogo with the Teide Volcanic Complex on Tenerife, where a lateral collapse of the Las Cañadas stratovolcano also formed a large depression (the Caldera de Las Cañadas), now partially filled with the 3718 m‐high Teide stratocone. However, important geological differences also exist and probably relate to the contrasting evolutionary stages of both islands. The Las Cañadas volcano on Tenerife formed at a late post‐erosional stage, with predominantly evolved (trachyte and phonolite) magmas, while at Fogo basaltic volcanism is still dominant.